2020
DOI: 10.3390/w12030853
|View full text |Cite
|
Sign up to set email alerts
|

Recharge–Discharge Relations of Groundwater in Volcanic Terrain of Semi-Humid Tropical Highlands of Ethiopia: The Case of Infranz Springs, in the Upper Blue Nile

Abstract: The major springs in the Infranz catchment are a significant source of water for Bahir Dar City and nearby villages, while sustaining the Infranz River and the downstream wetlands. The aim of the research was to understand the hydrogeological conditions of these high-discharge springs and the recharge–discharge relations in the Infranz catchment. The Infranz catchment is covered by highly pervious and young quaternary volcanic rocks, consisting of blocky, fractured, and strongly vesicular scoriaceous basalt. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Tigabu, et al [83] studied the impact of rainfall variability on the groundwater head, and found that the peak of the groundwater head occurs one to three months after the peak of the rainfall. Nigate, et al [84] described how the average annual groundwater recharge calculated using the SMB approach for the five years (2012-2016) is 748 mm, or 51% of the rainfall.…”
Section: Modelling Approaches Of Studies In the Lake Tana Basinmentioning
confidence: 99%
See 1 more Smart Citation
“…Tigabu, et al [83] studied the impact of rainfall variability on the groundwater head, and found that the peak of the groundwater head occurs one to three months after the peak of the rainfall. Nigate, et al [84] described how the average annual groundwater recharge calculated using the SMB approach for the five years (2012-2016) is 748 mm, or 51% of the rainfall.…”
Section: Modelling Approaches Of Studies In the Lake Tana Basinmentioning
confidence: 99%
“…Statistical analysis was employed in the Lake Tana basin to assess the impact of land and water management on hydrological processes [35,64,79,80]. In some publications, statistical models were used to assess: (1) the trend of rainfall and runoff, e.g., [126,127]; (2) groundwater recharge, e.g., [84]; (3) soil erosion, e.g., [128]; (4) lake level, e.g., [56,[129][130][131]; (5) phosphorus/dynamic, e.g., [132,133]; (6) sediment, e.g., [134][135][136]; (7) streamflow, e.g., [100,137]; and (8) water balance [138]. Statistical models were used to the address the hydrological response at the basin, subbasin and plot scale.…”
Section: Modelling Approaches Of Studies In the Lake Tana Basinmentioning
confidence: 99%
“…The basin has three major aquifers: the Tertiary volcanic, the Quaternary volcanic, and the alluvio lacustrine sediments (Kebede, 2012;Nigate et al, 2016). The Trap Series (Oligocene to Miocene) volcanic flows and edifices, Quaternary basalt and Quaternary sediments (comprises alluvial lake deposits) are the main geological units of the basin and mainly found in the highlands and cliffs, in the lowlands and the floodplain along the lake coastline (Prave et al, 2016;Nigate et al, 2020). The surface area of the basin is dominated by Tarmaber Basalt with intercalated tuffs and basaltic lava flows (SMEC, 2008a).…”
Section: Geology and Soil Characteristicsmentioning
confidence: 99%
“…Angereb reservoir is the main source of potable water for Gonder town (Getachew and Melesse 2012). Nigate et al (2020) reported that, since 2002, Areke and Lomi springs have been supplying municipal water for Bahir Dar town and the Infranz springs are being constructed to provide additional water supplies.…”
Section: Water For Drinking and Domestic Usementioning
confidence: 99%